Increased photocatalytic activity induced by TiO2/Pt/SnO2 heterostructured films - Testoni, Glaucio O. [UNESP]; Amoresi, Rafael A.C. [UNESP]; Lustosa, Glauco M.M.M. [UNESP]; Costa, João P.C. [UNESP]; Nogueira, Marcelo V. [UNESP]; Ruiz, Miguel [UNESP]; Zaghete, Maria A. [UNESP]; Perazolli, Leinig A. [UNESP] (Elsevier, 2018)
In this work, a high photocatalytic activity was attained by intercalating a Pt layer between SnO2 and TiO2 semiconductors, which yielded a TiO2/Pt/SnO2 - type heterostructure used in the discoloration of blue methylene (MB) solution. The porous films and platinum layer were obtained by electrophoretic deposition and DC Sputtering, respectively, and were both characterized morphologically and structurally by FE-SEM and XRD. The films with the Pt interlayer were evaluated by photocatalytic activity through exposure to UV light. An increase in efficiency of 22% was obtained for these films compared to those without platinum deposition. Studies on the reutilization of the films pointed out high efficiency and recovery of the photocatalyst, rendering the methodology favorable for the construction of fixed bed photocatalytic reactors. A proposal associated with the mechanism is discussed in this work in terms of the difference in Schottky barrier between the semiconductors and the electrons transfer and trapping cycle. These are fundamental factors for boosting photocatalytic efficiency.
Keywords: Films; Interface; Oxides; Photocatalysis